Hepatitis E virus infection in pigs: a first report from Zambia. Issue 1 (1st January 2021) - Chambaro, Herman M.; Sasaki, Michihito; Muleya, Walter; Kajihara, Masahiro; Shawa, Misheck; Mwape, Kabemba E.; Harima, Hayato; Qiu, Yongjin; Hall, William W.; Fandamu, Paul; Squarre, David; Simulundu, Edgar; et al.
ABSTRACT: While evidence suggests presence of HEV infection in humans in Zambia, currently, there is no information on its occurrence in domestic pigs. Here, we investigated the presence of HEV antibodies and genome in domestic pigs in Zambia. Sera ( n  = 484) from domestic pigs were screened for antibodies against HEV by ELISA while genome detection in fecal ( n  = 25) and liver ( n  = 100) samples from slaughter pigs was conducted using nested RT–PCR assay. Overall, seroprevalence was 47.7% (231/484) while zoonotic genotype 3 HEV RNA was detected in 16.0% (20/125) of slaughtered pigs. This is the first report to highlight occurrence of HEV infection in domestic pigs in Zambia. This finding suggests possible contamination of the pork supply chain. Moreover, there is a potential risk of zoonotic transmission of HEV to abattoir workers, pig farmers and handlers.